Evaluasi Pemeliharaan Taman Bungkul Surabaya - Cici Susilowati Pan; Ni Luh Made Pradnyawathi (Nandur, 2023)
Bungkul Park is one of city parks in Surabaya located on Jalan Raya Darmo, Wonokromo District, Surabaya. As a park that has many visitors and become the center of community activities in Surabaya, good maintenance is very important to maintain the comfort of visitors and the beauty of the park. This research aims to evaluate the maintenance of Bungkul Park from December 2019 to June 2023. The research method used is a descriptive method. Data in this research was collected by direct observation in Bungkul Park, interviewing park maintenance officers, surveying visitors through a questionnaire containing 20 questions about cleanliness, beauty, comfort, order, and security to 30 visitors to Bungkul Park, and studies through literature. Based on the results of the research conducted, the condition of the facilities at Bungkul Park is quite good, and the implementation of maintenance activities at Bungkul Park is carried out based on conditions and not on a schedule. The tools and materials used for park maintenance are quite complete and adequate. Based on the results of a survey on visitors' perceptions of Bungkul Park regarding cleanliness, beauty, order, and security, it is quite good. The author's suggestion is based on research, namely that it is necessary to have standard operating procedures for carrying out garden maintenance in writing and submitting routine maintenance activities, as well as installing plant identity boards so that visitors receive education about the types of plants in Bungkul Park.